2009
DOI: 10.1364/oe.17.018703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of storage induced outgassing organic contamination on laser induced damage of silica optics at 351 nm

Abstract: The impact of storage conditions on laser induced damage density at 351 nm on bare fused polished silica samples has been studied. Intentionally outgassing of polypropylene pieces on silica samples was done. We evidenced an important increase of laser induced damage density on contaminated samples demonstrating that storage could limit optics lifetime performances. Atomic Force Microscopy (AFM) and Gas Chromatography -Mass Spectrometry (GC-MS) have been used to identify the potential causes of this effect. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…For organic contaminant, it often exists as gaseous molecules or nonvolatile residues (NVRs). Gaseous organic contaminants involve airborne molecular contaminations (AMCs) [10] and outgassing from surrounding materials [11]. NVRs involve liquid and solid phase organic contaminants deposited on the surface of optical components [12].…”
Section: Introductionmentioning
confidence: 99%
“…For organic contaminant, it often exists as gaseous molecules or nonvolatile residues (NVRs). Gaseous organic contaminants involve airborne molecular contaminations (AMCs) [10] and outgassing from surrounding materials [11]. NVRs involve liquid and solid phase organic contaminants deposited on the surface of optical components [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that various levels of damage occur to laser glass during normal laser operations [9,[13][14][15]. The damage phenomenon has nearly always been associated with the introduction of extrinsic (external) particulate contamination such as the inadvertent exposure of gaskets to laser resulting in the generation of massive amounts of burned particles which form an aerosol and eventually settle everywhere inside the laser cavity.…”
Section: Laser-induced Damage Due To Contamination In Sg-iii Laser Famentioning
confidence: 99%
“…In dielectric materials irradiated by nanosecond pulses, if the wavelength is far from the absorption bands, laser damage in optical materials is mainly initiated by nanometric defects that absorb the laser energy, inducing a fast temperature rise and a subsequent plasma that will lead to mechanical failure due to extreme temperatures and pressures [35]. For surfaces, the initiating defects are often linked to polishing residues [36], fractures [37,38], or contamination [39]. If the surface is coated, different additional limiting defects can be found in the multilayer system: Nodules [40], substrate contaminants [41], impurities coming from the coating chamber or from the source material [42,43], voids, grain boundaries.…”
Section: Numerical Illustrationsmentioning
confidence: 99%